A Study on Awareness, Coverage and Willingness to Avail Health Insurance among the Residents of a Rural Area in Central Karnataka - Netra G; BA Varadaraja Rao (Medsci Publications, 2019)
Introduction: Health insurance is defined as "an individual or group purchasing health care coverage in advance by paying a fee called premium", which helps to defer, delay, reduce or avoid payment for health care incurred by individuals and households. As similar studies were lacking in this area the present study was undertaken to know the awareness, subscription in rural area. Objectives: To assess the awareness, coverage and willingness to avail health insurance by the residents of rural practice area of SSIMSRC, Davanagere. Methods: The present cross sectional study was conducted in the RHTC of SSIMSRC, Davangere from May-July 2016. A sample of 600 families was visited by systematic random sampling and data was collected from the head of the family with informed consent using a predesigned, pretested questionnaire by house to house in- terview. Analysis was done using SPSS v10 and Chi-square, re- gression analysis tests were applied for association. Results: The awareness, coverage and willingness to avail health insurance were 65.7%, 45.5% and 77.1% among the total families (600) studied respectively. Conclusion: Enrolment centres should be set up in each village for easy accessibility and the premiums should be customized to indi- vidual levels to benefit the poorer section of the community.